Chronic Cortical Cerebral Microinfarcts Slow Down Cognitive Recovery After Acute Ischemic Stroke. Issue 6 (June 2019) - Sagnier, Sharmila; Okubo, Gosuke; Catheline, Gwenaëlle; Munsch, Fanny; Bigourdan, Antoine; Debruxelles, Sabrina; Poli, Mathilde; Olindo, Stéphane; Renou, Pauline; Rouanet, François; Dousset, Vincent; Tourdias, Thomas; et al.
Abstract : Background and Purpose—: Cortical cerebral microinfarcts (CMIs) have been associated with vascular dementia and Alzheimer disease. The aim of the present study was to evaluate the role of cortical CMI detected on 3T magnetic resonance imaging, on the evolution of cognition during the year following an acute ischemic stroke. Methods—: We conducted a prospective and monocentric study, including patients diagnosed for a supratentorial ischemic stroke with a National Institutes of Health Stroke Scale score ≥1, without prestroke dementia or neurological disability. Cortical CMIs were assessed on a brain 3T magnetic resonance imaging realized at baseline, as well as markers of small vessel disease, stroke characteristics, and hippocampal atrophy. Cognitive assessment was performed at 3 time points (baseline, 3 months, and 1 year) using the Montreal Cognitive Assessment, the Isaacs set test, and the Zazzo's cancellation task. Generalized linear mixed models were performed to evaluate the relationships between the number of cortical CMI and changes in cognitive scores over 1 year. Results—: Among 199 patients (65±13 years old, 68% men), 88 (44%) had at least one cortical CMI. Hypertension was the main predictor of a higher cortical CMI load (B=0.58, P =0.005). The number of cortical CMI was associated with an increase time at the Zazzo's cancellation task over 1 year (B=3.84, P =0.01), regardless of the other magnetic resonance imaging markers, stroke severity, and demographic factors. Conclusions—: Cortical CMIs are additional magnetic resonance imaging markers of poorer processing speed after ischemic stroke. These results indicate that a high load of cortical CMI in patients with stroke can be considered as a cerebral frailty condition which counteracts to the recovery process, suggesting a reduced brain plasticity among these patients. Abstract : Supplemental Digital Content is available in the text.